2020
DOI: 10.1515/chem-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermal properties of bio-based microcapsules intended for textile applications

Abstract: AbstractThe thermal properties of bio-based phase change material (PCM) microcapsules and their separate components, core and shell, were investigated considering the influence of used thermal enhancer. As a core, bio-based PCM, capric acid (CA), was used. Biodegradable material, such as polylactic acid (PLA), was used as a shell. To improve the thermal conductivity of PLA/CA microcapsules, the multiwall carbon nanotubes (MWCNTs) were used as a thermal enhancer. Composites of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hence, the optimum concentration was specified as a range between 0.5% and 1%. [58] As can be seen from these compiled studies, thermal conductivity and phase change enthalpies were not reported, in detail, in most previous studies. Therefore, in this study, the effect of graphene, a carbon-based thermal conductive material, on the thermal properties of PCM microcapsule-coated polyester woven fabrics was investigated.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hence, the optimum concentration was specified as a range between 0.5% and 1%. [58] As can be seen from these compiled studies, thermal conductivity and phase change enthalpies were not reported, in detail, in most previous studies. Therefore, in this study, the effect of graphene, a carbon-based thermal conductive material, on the thermal properties of PCM microcapsule-coated polyester woven fabrics was investigated.…”
Section: Introductionmentioning
confidence: 89%
“…[42] Although there are many studies on thermal conductivity enhancement of PCM microcapsules, there are limited number of studies investigating the thermal conductivity properties of PCM-microcapsule-coated fabrics. [48,56,58,59] Shemsadi et al developed a polyacrylamide (PAAm) membrane by coating PCM microcapsules (mPCMs) with graphene oxide (GO) and reduced graphene oxide (rGO) on polypropylene (PP) nonwovens with a micrometer adjustable film applicator. Thermal conductivity of the PAAm hydrogel-coated membranes (0.0024 W/m.K) was enhanced three times (0.0063 W/m.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulated latent heat energy is released when the PCM re-solidifies, and the transition process is reversible. Typical organic PCMs are paraffin hydrocarbons or lipids with a melting point close to body temperature [37][38][39][40][41][42][43][44][45][46]. In addition to classical PCMs, photothermal energy conversion materials also perform similar functionalities.…”
Section: Microcapsules In Functional Textile Productsmentioning
confidence: 99%
“…3D polyester knitted fabric with enhanced thermal properties. [39] Ethyl cellulose. Immortelle essential oil.…”
Section: Emulsification and Solvent Evaporationmentioning
confidence: 99%
“…MEPCMs can be biodegradable by using biodegradable shell materials and core materials. Using capric acid as the biodegradable PCMs, degradable polylactic acid as the shell materials, Skurkytė-Papievienė et al 92 prepared the biodegradable MEPCMs, and added MWCNTs as the heat conduction enhancement fillers. Based on the experimental results, they found that the obtained MEPCMs are biodegradable and their thermal conductivity is enhanced.…”
Section: Microencapsulation Of Pcms With Hybrid Shellsmentioning
confidence: 99%